PEMERTAHANAN BAHASA JAWA MELALUI KULIAH KEPEWARAAN DI IAIN TULUNGAGUNG - Mohamad Jazeri (Jurnal Bahasa Lingua Scientia, 2019)
Some studies show that Javanese language is now rarely used by Javanese people in their daily communication. Some Javanese prefer to communicate with national language and foreign language to Javanese language. As a result, only a few Javanese people who able to speak Javanese well. Therefore, to maintain Javanese Language IAIN Tulungagung conducts a Javanese Langauage course named Kepewaraan. This stusdy investigates Javanese Language maintenance through teaching Kepewaraan at IAIN Tulungagung. This study aims at describing the purpose, materials, methods, and evaluations of teaching Kepewaraan at IAIN Tulungagung. This study is a qualitative with sociolinguistics approach. The data were collected through interview, observasion, and documentation.  Data analysis reveals (1) the purpose of teaching Kepewaraan is to maintain Javanese language by digging, learning, and improving Javanese Language, (2) materials of Kepewaraan cover Javanese language and literature, speech levels, and rapping speech, (3) teaching methods implemented were immersion and drill, and (4) teaching evaluasions used were written and oral tests.